Bioinspired Diselenide‐Bridged Mesoporous Silica Nanoparticles for Dual‐Responsive Protein Delivery. Issue 29 (28th May 2018) - Shao, Dan; Li, Mingqiang; Wang, Zheng; Zheng, Xiao; Lao, Yeh‐Hsing; Chang, Zhimin; Zhang, Fan; Lu, Mengmeng; Yue, Juan; Hu, Hanze; Yan, Huize; Chen, Li; et al.
Abstract: Controlled delivery of protein therapeutics remains a challenge. Here, the inclusion of diselenide‐bond‐containing organosilica moieties into the framework of silica to fabricate biodegradable mesoporous silica nanoparticles (MSNs) with oxidative and redox dual‐responsiveness is reported. These diselenide‐bridged MSNs can encapsulate cytotoxic RNase A into the 8–10 nm internal pores via electrostatic interaction and release the payload via a matrix‐degradation controlled mechanism upon exposure to oxidative or redox conditions. After surface cloaking with cancer‐cell‐derived membrane fragments, these bioinspired RNase A‐loaded MSNs exhibit homologous targeting and immune‐invasion characteristics inherited from the source cancer cells. The efficient in vitro and in vivo anti‐cancer performance, which includes increased blood circulation time and enhanced tumor accumulation along with low toxicity, suggests that these cell‐membrane‐coated, dual‐responsive degradable MSNs represent a promising platform for the delivery of bio‐macromolecules such as protein and nucleic acid therapeutics. Abstract : Diselenide‐bond‐containing organosilica moieties are introduced into the framework of mesoporous silica to fabricate biodegradable mesoporous silica nanoparticles (MSNs) with an oxidative and redox dual‐responsive degradable feature. After surface cloaking with cancer‐cell‐derived membrane fragments, these bioinspired RNase‐A‐loaded MSNs exhibit homologous targeting and immune escape abilities, leading to efficient in vitro and in vivo anti‐cancer performance along with low toxicity.